Mekanisme Transmisi Kebijakan Moneter di Indonesia Melalui Sistem Moneter Syariah - Sugianto Sugianto (HUMAN FALAH: Jurnal Studi Ekonomi dan Bisnis Islam, 2015)
This study aims to identify the monetary transmission process from Islamic financing of Islamic banks mechanisms in Indonesia and prove whether the Islamic financing mechanism will create a balance between the monetary and the real sector, causing a reduction in the rate of inflation. The variables of this study were the rate of inflation, PUAS, SBIS and Islamic financing of Islamic banks using time series data. Data were analyzed using the VAR. The results showed that in the short term total PUAS, total SBIS and total Islamic financingof Islamic bank in a stable relationship to therate of inflation.